Learning Analysis with ARIAS Model on Students' Critical Thinking Skills Reviewed from Learning Styles - Hamidah Hamidah; Jaka Wijaya Kusuma; Ilmadi Ilmadi (AlphaMath : Journal of Mathematics Education, 2022)
A person who can think critically in mathematics means having a high level of ability and is a fundamental ability that students must have to learn mathematics. The research aims to determine the influence of understanding the ARIAS model on students' critical thinking skills in terms of learning style. This type of research is quasi-experimental with a post-test nonequivalent control group design. The research population is a student majoring in mathematics education at Bina Bangsa University, then selected two classes as research subjects. The acquisition of data from mathematical critical thinking skills tests and learning style questionnaires was then processed with the ANOVA (Analysis of Variance) test. The results showed a significant difference in mathematical necessary thinking skills between students and ARIAS learning and ordinary learning and judging from students' learning styles. There was a substantial difference in mathematical critical thinking skills. Furthermore, it is known that there is an interaction between the type of learning and its learning style towards students' mathematical necessary thinking skills.